Immittance Electroanalysis in diagnostics. - Patil, A; Bedatty Fernandes, F; Bueno, P; Davis, J (2014)
Impedance derived electroanalytical assays are inherently spectroscopic (frequency resolved) and potentially exceedingly sensitive indicators of interfacial change (such as target binding with an appropriate receptor). We introduce here the use of a portfolio of mathematically derived immittance functions and related components capable, from the same raw data sets, of enabling increased assay sensitivity and markedly shorter assay times in comparison to traditional impedance analyses. The methodology, applied herein to faradaic (redox probe amplified) and non-faradaic assays, requires no equivalent circuit analysis or prior assumption of response. It also enables the user to select and apply the most frequency-optimized reporter of interfacial change and to, thereafter, run rapid optimized analyses at single frequencies.